Evaluating the performance of Inspector General office of the Ministry of health in accordance with normative people and people results for the European excellence model EFQM 2013 - صيهود علي موات; حيدر زيد علي (Journal of Economics and Administrative Sciences, 2017)
Current research sought to evaluate the performance and results of employees in accordance with normative to people and people result for the European model of excellence EFQM 2013 quality management Foundation in the Inspector General’s Office/Ministry of health, so as to pursue a modern and advanced management methods in evaluating performance and the performance of the Office’s relationship with a citizen’s life, since it takes him beyond the accepted service capabilities today, but it became budget duties between dealers servicing responsibilities and future planning, financial control, competitiveness, human resources needs and maintaining quality and continuous improvement and development as well as The primary role of the human resource in achieving continuous improvement, is the spirit of the principle underpinning the European Foundation for quality management excellence model design. Use the case study methodology researcher, through data collection checklist for evaluation in addition to interviews, the answer has been analysed using percentages and arithmetic, and indicate their strengths for the purpose of strengthening, and vulnerabilities for patch and calendar, and improvement opportunities to exploit and not to be missed. Special evaluation criteria were generally.